Shesh Narain Singh , R. K. Doharey and Shalini Srivastava - Shesh Narain Singh , R. K. Doharey and Shalini Srivastava, (Indian Journal of Extension Education, 2014)
This study was conducted in four main agricultural universities in Uttar Pradesh, by interviewing 300 respondents whowere selected through proportionate random sampling technique on the criteria of having four year degree programme ofB.Sc.(Ag.), two year degree programme M.Sc.(Ag.) and three year degree programme Ph.D.(Ag.). The study depictedthat the highest number of respondents in age category of 22 to 26 years belonged to nuclear families (79%) and having 5-10 members in their families (72%). Except 7 per cent respondents all were unmarried and backward caste respondentswere more in comparison to other categories of caste. The economic motivation, risk orientation and value orientationswere observed of medium levels. The mobile phone is most useful communication media. The agriculture was observedas main occupation of majority of the respondent's families and having annual income of `100001 to 200000 (31%). The51 per cent respondents were found having pucca type houses, 35 per cent of the respondents were found in the landholding category of small farmers. 64.66 per cent medium level of decision pattern of father. The maximum number ofrespondents was observed in medium category of communication technology use in day and most usefulness ofcommunication technologies in career preferences was mobile phone. The purpose in use of communication Technologywas 'computer information retrieval or data updating' ranked first. The civil cervices or administrative jobs were foundmost preferred jobs followed by state government job by the agriculture students.